MAKNA FILOSOFI DAN NILAI-NILAIYANG TERKANDUNG DALAM TARI KLANA RAJAGAYA YOGYAKARTA - Ida Gustria I., dan Luvia P., Nur Indrawati, Damar Kasyiyadi, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2008)
This research studies the philosophical message and values in the dance “KlanaRaja” of Yogyakarta style. The philosophical message here is the one in Mataram dancephilosophy as well as the depth of philosophy in every movement style and its educationalvalues.Classical dance which is full of values has not been known by society. This dancehas rigid rules. In its realization, classical dance conveys philosophical values with thedeep philosophical background . There are two important things which need to beunderstood in order to be able to do classical dance perfectly, involving understandingphilosophical base and its character and then perfect its skill of dance techniques.Yogyakarta classical dances are familiar with basic norms or rules in performingdance or character. The basic norms are pasemon (face expression) and pandengan(eye gaze), pacak gulu (neck movement), deg (body movement), cethik (thigh), mlumahingpupu (breaking of thigh position), nyelekenthing (toe upright) and mendak.. Yogyakartaclassical dances are also known for their rhythm sensitivity such as gendhing (javanesemusical instruments) rhythm sensitivity, movement rhythm sensitivity, and spacerhythm sensitivity. The dance ‘Klana Raja’ tells about the king who wanders to reachhis desire. The dance created by KRT. Condroradono in 1962 is a learning material ofdance department students, of KONRI (Indonesian dance conservatory) which is nowknown as SMK N I Kasihan, Bantul, DIY.Key words: classical dance, Klana Raja, philosopical message